FangTianSim: High-Level Cycle-Accurate Resistive Random-Access Memory-Based Multi-Core Spiking Neural Network Processor Simulator - Wei, Jinsong; Wang, Zhibin; Li, Ye; Lu, Jikai; Jiang, Hao; An, Junjie; Li, Yiqi; Gao, Lili; Zhang, Xumeng; Shi, Tuo; Liu, Qi (Frontiers in Neuroscience, 2022)
Realization of spiking neural network (SNN) hardware with high energy efficiency and high integration may provide a promising solution to data processing challenges in future internet of things (IoT) and artificial intelligence (AI). Recently, design of multi-core reconfigurable SNN chip based on resistive random-access memory (RRAM) is drawing great attention, owing to the unique properties of RRAM, e.g., high integration density, low power consumption and processing-in-memory (PIM). Therefore, RRAM-based SNN chip may have further improvements in integration and energy efficiency. The design of such a chip will face the following problems: significant delay in pulse transmission due to complex logic control and inter-core communication; high risk of digital, analog and RRAM hybrid design; nonideal characteristics of analog circuit and RRAM. In order to effectively bridge the gap between device, circuit, algorithm, and architecture, this paper proposes a simulation model - FangTianSim, which covers analog neuron circuit, RRAM model and multi-core architecture and its accurate is at clock level. This model can be used to verify the functionalities, delay, power consumption of SNN chip. This information can not only be used to verify the rationality of the architecture, but also guide the chip design. In order to map different network topologies on the chip, SNN representation format, interpreter and instruction generator are designed. Finally, the function of FangTianSim is verified on liquid state machine (LSM), fully connected neural network (FCNN) and convolutional neural network (CNN).